Fostering Self-Confidence: The Impact of Online-Based Hybrid Learning on English Speaking Proficiency - Nur, Syauqiyah Awaliyah Alfiani; Noni, Nurdin; Korompot, Chairil Anwar (Pascasarjana Universitas Negeri Makassar, 2025)
This study explores the impact of an online-based hybrid learning model on students’ self-confidence in speaking English as a foreign language. Conducted at Universitas Negeri Makassar, the research involved 20 second-semester English education students enrolled in an Interactive Speaking course. Employing a qualitative approach, data were collected through semi-structured interviews and analysed using NVivo software to uncover themes related to learners' confidence levels. The hybrid learning model integrated both synchronous platforms (e.g., Zoom, Google Meet, WhatsApp) and asynchronous tools (e.g., Google Classroom, Instagram, YouTube, SYAM-OK), offering students flexibility and multiple forms of engagement. Findings revealed three distinct self-confidence profiles among students high, moderate, and low. Students with high self-confidence reported enhanced participation and reduced anxiety due to the hybrid model's supportive structure. Those with moderate self-confidence highlighted the benefits of decreased social pressure and the ability to control their learning environment. In contrast, students with low self-confidence continued to struggle despite the flexible format, citing persistent fear of judgment and speaking errors. The study concludes that while online-based hybrid learning can effectively foster self-confidence in speaking for many students, it may not suffice for learners with deeply rooted anxiety. These findings underscore the need for tailored pedagogical strategies that combine technological affordances with targeted confidence-building interventions to ensure inclusive and effective language instruction.